AN INVESTIGATION OF SOURCES OF SPEAKING ANXIETY AMONG THE STUDENTS OF AIRCRAFT MACHINING MAJOR - Sophie Amalia Karimah, - (2022)
Kecemasan berbicara dapat menjadi salah satu faktor yang melemahkan dalam berbicara. English for Specific Purposes atau ESP adalah pengejaran bahasa Inggris yang berfokus pada situasi belajar dan mengajar bahasa Inggris tertentu yang terkait erat dengan karir target. Dimana tujuannya berbeda dari pengajaran bahasa Inggris umum, penelitian ini menyelidiki sumber kecemasan berbicara siswa dari siswa sekolah menengah kejuruan di Bandung. Desain penelitian yang digunakan dalam penelitian ini adalah pengumpulan data kualitatif yaitu wawancara dan observasi kelas. Partisipan dalam penelitian ini berjumlah 13 mahasiswa, dan 7 diantaranya merupakan mahasiswa yang mengikuti wawancara terkait penelitian. Pengumpulan data dilakukan dengan menggunakan metode wawancara terbuka terhadap 7 dari 13 siswa dengan 27 pertanyaan yang berkaitan dengan penelitian, kemudian dilanjutkan dengan observasi kelas dengan meminta siswa untuk melakukan presentasi di depan kelas. Analisis data dilakukan dengan hasil yang diperoleh dari wawancara dan observasi kelas dari enam sumber kecemasan berbicara yang diidentifikasi oleh Young (1991). Ada tiga penyebab yang dialami siswa dalam berbicara bahasa Inggris, yaitu kecemasan personal-interpersonal, keyakinan siswa dalam belajar bahasa Inggris, dan keyakinan guru dalam pengajaran bahasa Inggris. Dalam membantu siswa dalam mengembangkan keterampilan dan pengetahuan khususnya dalam pelajaran bahasa Inggris, guru harus mewaspadai kecemasan di kalangan siswa sejak awal. Kata kunci: Pemesinan pesawat, EFL, FLA, keterampilan berbicara An Investigation of Sources of Speaking Anxiety among the Students of Aircraft Machining Major ABSTRACT Speaking anxiety could be one of the debilitating factors in speaking. English for Specific Purposes or ESP is an English language pursuit that focuses on particular learning and teaching English situations related closely to the target career. Where the goals differ from general English teaching, this study investigated the source of students' speaking anxiety of vocational high school students in Bandung. The research design used in this study is a qualitative collection of data, namely interviews and class observations. Participants in this study amounted to 13 students, and 7 of them were students who participated in interviews related to the research. The data collection was carried out using the open-ended interview method of 7 of 13 students with 27 questions related to research, then continued with class observations by asking students to make presentations in front of the class. The data analysis was carried out with the results obtained from interviews and class observations from six sources of speaking anxiety identified by Young (1991). There were three causes that the students experienced in speaking English, namely personal-interpersonal anxieties, students' beliefs in learning English, and teachers' beliefs in English teaching. In assisting students in developing skills and knowledge, especially in English lessons, teachers must be aware of anxiety among students at the beginning. Key words: Aircraft machining, EFL, FLA, speaking skills